On the aeroacoustic characterization of a robust trailing-edge serration - Alper Celik (Physics of Fluids, 2021)
This paper presents an experimental study on the aeroacoustics of a flat plate rig with a highly instrumented serrated trailing-edge. The role of near-field flow properties, namely, surface pressure fluctuations and spanwise coherence, in the noise suppression capability of serration is not properly understood. The results from this test rig aim to provide additional insight into the effects of the serration on the hydrodynamic field (flow field) and the scattering of the pressure waves along the trailing-edge. Despite its unconventional size, beamforming results showed a significant reduction of far-field noise over a broadband frequency range. The associated flow field is characterized by mean and spectral analyses of static and dynamic surface pressure measurements as well as hot-wire measurements. The mean pressure coefficient results and the boundary layer velocity profiles over the serrated trailing-edge showed minute differences compared to the baseline straight trailing-edge. However, the frequency-dependent energy content of the unsteady surface pressure fluctuations demonstrates an elevated energy region around the serration edges at low frequencies. Although there is an increase in the energy content of the low frequency pressure fluctuations on the serrated trailing-edge, a significant phase difference of the pressure waves is observed, which may be indicative of destructive interference. The temporal studies regarding the unsteady surface pressure fluctuations corroborate the presence of quasi-periodic large scale structures emanating from the serration edges.